Xylella fastidiosa Infection Reshapes Microbial Composition and Network Associations in the Xylem of Almond Trees - Anguita-Maeso, Manuel; Ares-Yebra, Aitana; Haro, Carmen; Román-Écija, Miguel; Olivares-García, Concepción; Costa, Joana; Marco-Noales, Ester; Ferrer, Amparo; Navas-Cortés, Juan A.; Landa, Blanca B. (Frontiers in Microbiology, 2022)
Xylella fastidiosa (Xf) represents a major threat to important crops worldwide including almond, citrus, grapevine and olives. Nowadays, there are no efficient control measures for Xf, and the use of preventive measures and host resistance represent the most practical disease management strategies. Research on vascular-associated microorganisms is gaining especial interest as an innate natural defense of plants to cope against infection by xylem-inhabiting pathogens. The objective of this research has been to characterize by NGS analysis the microbial communities residing in the xylem sap of almond trees affected by almond leaf scorch disease (ALSD) in a recent Xf outbreak occurring in Alicante province, Spain. We also determined the community composition changes and the network associations occurring between xylem-inhabiting microbial communities and Xf. For that, a total of 91 trees with or without ALSD symptoms were selected from a total of eight representative orchards located in five municipalities within the Xf-demarcated area. Xf infection on each tree was verified by qPCR analysis, with 54% of trees being tested Xf-positive. Globally, Xylella (27.4%), Sphingomonas (13.9%) and Hymenobacter (12.7%) were the most abundant bacterial genera, whereas Diplodia (30.18%), a member of the Family Didymellaceae (10.7%), and Aureobasidium (9.9%) were the most predominant fungal taxa. Furthermore, Principal Coordinate Analysis of Bray-Curtis and weighted UniFrac distances differentiated almond xylem bacterial communities mainly according to Xf infection in contrast to fungal community structure that was not closely related to the presence of the pathogen. Similar results were obtained when Xf reads were removed from the bacterial dataset, although the effect was less pronounced. Co-occurrence network analysis revealed negative associations among four amplicon sequence variants (ASVs) assigned to Xf with different bacterial ASVs belonging to 1174-901-12, Abditibacterium, Sphingmonas, Methylobacterium-Methylorubrum, Modestobacter, Xylophilus and a non-identified member of the Family Solirubrobacteraceae. Determining the close-fitting associations between xylem-inhabiting microorganisms and Xf may help to reveal specific microbial players associated with the suppression of ALSD under high Xf inoculum pressure. These identified microorganisms are good candidates to be tested in planta, to produce almond plants more resilient to Xf infection when inoculated by endotherapy, contributing to suppress ALSD.